Conceptual change: A powerful framework for improving science teaching and learning - Duit, Reinders; Treagust, David (International Journal of Science Education, 2003)
In this review, we discuss (1) how the notion of conceptual change has developed over the past three decades, (2) giving rise to alternative approaches for analysing conceptual change, (3) leading towards a multiperspective view of science learning and instruction that (4) can be used to examine scientific literacy and (5) lead to a powerful framework for improving science teaching and learning.